The aquatic and littoral forms of the Patagonian frog Atelognathus patagonicus (Batrachylinae): new molecular evidence - Martinazzo, Liza B.; Basso, Néstor G.; Úbeda, Carmen A. (Zootaxa, 2011)
Atelognathus patagonicus is one of the eight species included in the Patagonian genus Atelognathus, an endemic frog occurring in the system of endorheic basaltic lagoons of the Laguna Blanca National Park (PNLB), Neuquén, Argentina. Based on morphological data, Cei & Roig (1968) described two forms of A. patagonicus, which they called “aquatic” and “littoral”. These morphotypes were first suggested to belong to different species, but later, Cei (1972) proposed that both forms represent a balanced polymorphism within A. patagonicus. More recently, an ecomorphological study showed that aquatic and littoral are reversible forms of the same individual (phenotypic plasticity). In this paper we compare the morphotypes of A. patagonicus using nucleotide sequences of the mtDNA (cytochrome b and control region) in order to test the existence of genetic differentiation between the aquatic and littoral forms. In addition, we present data of genetic variability of A. patagonicus from the Laguna Blanca system. We did not detect genetic differentiation between littoral and aquatic morphotypes for both genes studied. This observation is consistent with the hypothesis of phenotypic plasticity. In contrast with the expected results for low vagility organisms, the diversity index observed in A. patagonicus revealed a low genetic variability.